Power of the pill or power of abortion? Re-examining the effects of young women's access to reproductive control - Caitlin Knowles Myers (Institute for the Study of Labor (IZA), 2012)
Recent research postulating that the diffusion of confidential access to the birth control pill to young women in the United States contributed to the dramatic social changes of the late 1960s and 1970s has not adequately accounted for the largely contemporaneous diffusion of access to abortion. Estimates using a new panel of data on state policies related to access to the pill and abortion indicate that while access to the pill may have played a role in the sexual revolution, it had little effect on the probabilities of entering into marriage and parenthood at a young age. In contrast, both the legalization of abortion and the enactment of laws permitting young unmarried women to consent to it led to substantial delays in marriage and motherhood.
Keywords: I18; J12; J13; 330; abortion; contraception; fertility; marriage; Schwangerschaftsabbruch; Empfängnisverhütungsmittel; Sozialer Wandel; Fruchtbarkeit; Ehe; USA